Certain Dietary Patterns Are Beneficial for the Metabolic Syndrome: Reviewing the Evidence - Calton, Emily; James, Tony; Pannu, Poonam; Soares, Mario (Elsevier Inc., 2014)
The metabolic syndrome (MetS) is a global public health issue of increasing magnitude. The Asia-Pacific region is expected to be hardest hit due to large population numbers, rising obesity, and insulin resistance (IR). This review assessed the protective effects of dietary patterns and their components on MetS. A literature search was conducted using prominent electronic databases and search terms that included in combination: diet, dietary components, dietary patterns, and metabolic syndrome. Articles were restricted to prospective studies and high quality randomized controlled trials that were conducted on humans, reported in the English language, and within the time period of 2000 to 2012. Traditional factors such as age, gender, physical activity, and obesity were associated with risk of MetS; however, these potential confounders were not always accounted for in study outcomes. Three dietary patterns emerged from the review; a Mediterranean dietary pattern, dietary approaches to stop hypertension diet, and the Nordic Diet. Potential contributors to their beneficial effects on prevalence of MetS or reduction in MetS components included increases in fruits, vegetables, whole grains, dairy and dairy components, calcium, vitamin D, and whey protein, as well as monounsaturated fatty acids, and omega-3 fatty acids. Additional prospective and high quality randomized controlled trial studies that investigate Mediterranean dietary pattern, the dietary approaches to stop hypertension diet, and the Nordic Diet would cement the protective benefits of these diets against the MetS.